Pelaksanaan Elemen Sastera dalam Pengajaran dan Pembelajaran Seni Bahasa Kurikulum Standard Sekolah Rendah (Jurnal Bahasa, 2013)
This paper will address the reading skills that are associated with the element of language arts and implemented in the Standard Curriculum for Primary Schools (KSSR) in stages beginning 2011. KSSR focused on the four skills of reading, writing, mathematics and reasoning in order to enhance the learning of the Malay language. In order to make this subject increasingly attractive and competitive, a Malay language curriculum consisting of a new element was introduced into the Malay KSSR, namely the language of "art edutainment" as one of the approaches to teaching and learning. Language arts refers to the ability of students to understand, express and appreciate the beautiful language through a fun-filled learning edutainment. As such, this study aimed to identify teacher confidence in the teaching and learning of language arts and to measure the extent to which teachers can apply literary elements and text to improve the effectiveness of students' reading skills . This study employed the descriptive approach and data were collected through questionnaires and interviews. The respondents selected comprised Malay primary school teachers. This study hypothesizes that teachers have a high level of confidence in the teaching and learning of language arts and are able to stimulate students' reading skills . The study also proposes that literature-based texts will be better able to build confidence and to enhance the ability.Keywords: literary elements, language arts, reading skills, edutainment, Standard Curriculum for Primary Schools (KSSR)